2023
DOI: 10.1007/s00787-023-02157-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation in children and young people with psychiatric disorders: a systematic review

Abstract: Transcranial direct current stimulation (tDCS) has demonstrated benefits in adults with various psychiatric disorders, but its clinical utility in children and young people (CYP) remains unclear. This PRISMA systematic review used published and ongoing studies to examine the effects of tDCS on disorder-specific symptoms, mood and neurocognition in CYP with psychiatric disorders. We searched Medline via PubMed, Embase, PsychINFO via OVID, and Clinicaltrials.gov up to December 2022. Eligible studies involved mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Meanwhile, the long-term effects of tDCS, particularly on developing brains have not been studied thoroughly. Data from tDCS use in children with neurodevelopmental and motor disorders does not show any serious long-term adverse effects[ 29 ]. But long-term follow-up studies in mood and anxiety disorders in children are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the long-term effects of tDCS, particularly on developing brains have not been studied thoroughly. Data from tDCS use in children with neurodevelopmental and motor disorders does not show any serious long-term adverse effects[ 29 ]. But long-term follow-up studies in mood and anxiety disorders in children are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is an accessible, safe, and inexpensive neuromodulation technique [1][2][3]. It has attracted growing research attention as a noninvasive intervention that improves the cognitive functioning scores of clinical patients and healthy individuals [4][5][6]. Initial studies suggested enhanced working memory performance after dorsolateral prefrontal cortex (dlPFC) tDCS stimulation (see review [7]).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported that most eligible studies (27 out of 33) involving multiple tDCS sessions in children and young people with psychiatric disorders, including ASD, reported improvement in at least one disorder‐specific symptom outcome measure. However, the evidence so far is insufficient to conclude firmly that tDCS can improve clinical symptoms, mood, or cognition 13 …”
mentioning
confidence: 99%
“…However, the evidence so far is insufficient to conclude firmly that tDCS can improve clinical symptoms, mood, or cognition. 13 A study protocol for a randomized, double-blind, sham-controlled clinical trial on adolescents with ASD comprised 10 anodal or sham tDCS sessions applied over the LDLPFC within 2 consecutive weeks. It provided information about the persistence of treatment effects and the clinical symptomatology up to 6 months after the end of the intervention.…”
mentioning
confidence: 99%